1988
DOI: 10.1016/0735-1097(88)92608-3
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-123 meta-iodobenzylguanidine scintigraphy: A noninvasive method to demonstrate myocardial adrenergic nervous system disintegrity in patients with idiopathic dilated cardiomyopathy

Abstract: Iodine-123 (I-123) meta-iodobenzylguanidine (MIBG) imaging was performed in 31 patients. Three patients were without cardiac disease and 28 had idiopathic dilated cardiomyopathy with various degrees of left ventricular dysfunction. The qualitatively assessed myocardial I-123 MIBG scintigrams and the myocardial versus mediastinal I-123 MIBG uptake ratio were related to I-123 MIBG activity and norepinephrine concentration determined from endomyocardial biopsy samples taken from the right side of the interventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(118 citation statements)
references
References 6 publications
5
110
0
3
Order By: Relevance
“…Our findings in patients with congestive heart failure and normal subjects were consistent with those of other studies 3,4 . Schofer et al 3 and Glowniak et al 4 showed that the lung uptake of 123 I-MIBG was slightly increased in DCM patients with congestive heart failure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings in patients with congestive heart failure and normal subjects were consistent with those of other studies 3,4 . Schofer et al 3 and Glowniak et al 4 showed that the lung uptake of 123 I-MIBG was slightly increased in DCM patients with congestive heart failure.…”
Section: Discussionsupporting
confidence: 83%
“…Iodine-123 MIBG ( 123 I-MIBG) scintigraphy has been widely used for the detection of various neuroendocrine tumors and the evaluation of adrenergic dysfunction in the heart [3][4][5] . 123 I-MIBG is also taken up by lung through a saturable, energy-requiring, soduium-dependent transport mechanism similar to biogenic amines, such as serotonin and norepinephrine [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…With progression of cardiac dysfunction there is diminished pre-synaptic function from loss of neurons and downregulation of NET-1, likely accounting for decreased cardiac uptake (lower H/M) in advanced disease. 52 Following the initial report by Kline et al of human cardiac 123 I-mIBG imaging, Schofer et al 65 were the first to describe a potential role for 123 I-mIBG imaging in HF, finding decreased cardiac uptake in 28 patients with idiopathic dilated cardiomyopathy that correlated inversely with LVEF, but surprisingly did not relate to circulating catecholamine. Prognostic utility was first reported in a 1992 landmark study by Merlet et al of 90 patients with advanced HF (NY Heart Association (NYHA) Class II-III symptoms and LVEF \45%), finding that H/M was superior to and independent of cardiac size on chest x-ray, echocardiographic enddiastolic diameter, and LVEF in predicting survival.…”
Section: Clinical Applications Heart Failurementioning
confidence: 99%
“…Abnormalities of myocardial uptake of 123 I-mIBG in patients with severe dilated cardiomyopathy were reported separately by Henderson et al 7 and Schofeld et al 3 In the following years, there was a vigorous debate on how best to evaluate abnormal mIBG uptake. Initial, 4, and 24 hours images as well as washout were evaluated but none seemed to perform as well as the simple heart-to-mediastinal (H/M) ratio.…”
mentioning
confidence: 99%
“…mIBG utilizes the same storage and release mechanisms as norepinephrine, but its lack of catabolism by the same enzymes as norepinephrine provides its ability to noninvasively evaluate the sympathetic nervous system. 3 Specific to the cardiac uses of this agent, it provides insight into the myocardial sympathetic nervous system and its impact of different disease states. 4 The myocardial uptake of these agents was first described in canine subjects in 1980 5 and in human subjects in 1981.…”
mentioning
confidence: 99%